1982
DOI: 10.1002/pd.1970020110
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound movement patterns of fetuses with chromosome anomalies

Abstract: Fetal movements were examined by ultrasound in 24 pregnancies in which an abnormal karyotype was detected in fetal cells and compared to ultrasound fetal movement patterns in normal pregnancies. The main features in fetuses with chromosome anomalies observed at 18-20 weeks of gestation are the persistence of global, jerky movements with twitches usually seen at 13-14 weeks of gestation in normal fetuses. This fetal motor behaviour is inconstant in trisomy 21. In trisomy 18 the hand deformities are easily detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 3 publications
2
24
0
Order By: Relevance
“…The autopsy results confirmed this finding. Interestingly, fetal hyperactivity with jerky movements was noted in 60% of our cases, in keeping with previous data from fetuses with Down syndrome or hypothyroidism [3,11]. One possible explanation of this finding is overexpression of central adrenergic receptors, as recently described in a mouse model of Down syndrome associated with high type II iodothyronine deiodinase activity in the brain [12].…”
Section: Discussionsupporting
confidence: 79%
“…The autopsy results confirmed this finding. Interestingly, fetal hyperactivity with jerky movements was noted in 60% of our cases, in keeping with previous data from fetuses with Down syndrome or hypothyroidism [3,11]. One possible explanation of this finding is overexpression of central adrenergic receptors, as recently described in a mouse model of Down syndrome associated with high type II iodothyronine deiodinase activity in the brain [12].…”
Section: Discussionsupporting
confidence: 79%
“…The need for fetal karyotyping has al ready been emphasized [6,7], The results of the French studies confirm and specify the frequency of chromosomal abnormalities in these situations.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, fetuses from 17 to 20 weeks made jerky or slow flexion and extension movements of the trunk, sometimes accompanied by movement of a single limb. Boue, Vignal, Aubrey, and Aleese (1982) reported that healthy fetuses at 18-20 weeks performed slow, supple, and harmonious movements with isolated leg movements, in contrast to the synchronized movements of the whole body with twitches and kicking, as frequently noted at 12-13 weeks. Moreover, some movement patterns occurred more frequently than others at 7-19 weeks of gestation.…”
Section: -D Ultrasonographic Observation Of the Entire Fetal Bodymentioning
confidence: 84%